2021
DOI: 10.3390/diseases9020025
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Literacy among Adolescents and Its Association with Eating Habits and BMI in Tripoli, Lebanon

Abstract: (1) Background: Adolescence is a period of increased autonomy and independent decision making; it determines health behaviors that can persist into the future. Individual factors like food choices and unhealthy lifestyle have an essential role in the development and prevention of obesity among adolescents and are associated with the nutrition literacy of parents and other adults. While the association of parents’ nutrition literacy with adolescent BMI has been addressed, there is still a scarcity of studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
2
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 56 publications
2
27
2
15
Order By: Relevance
“…Meanwhile, given the lack of proper awareness of their own body shape, obese children tend to make unhealthy food options ( 54 ). Increasing nutrition knowledge and skills through improving NL and promoting application of nutrition knowledge for healthy eating practices can reduce malnutrition in children ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, given the lack of proper awareness of their own body shape, obese children tend to make unhealthy food options ( 54 ). Increasing nutrition knowledge and skills through improving NL and promoting application of nutrition knowledge for healthy eating practices can reduce malnutrition in children ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature indicates that NL is significantly related to sociodemographic variables and healthy eating behavior [28,[36][37][38][39]. Many scholars have used the social-ecological model to identify multi-level factors that affect healthy eating behavior [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that health literacy mediated the relationship between sociodemographic variables and health-promoting behaviors/health outcomes [33][34][35]. Since NL is associated with healthy eating behavior and derived from health literacy [28,[36][37][38], and sociodemographic variables are also predictors of NL [38,39], we assume that NL may play a similar role to health literacy in mediating the effect of factors influencing healthy eating on healthy eating behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Nutrition literacy (NL) is associated with overall food habits ( 9 , 10 ). It is defined as obtaining, understanding, and using correct nutrition information and nutrition knowledge to make healthy food choices ( 11 ). Krause et al ( 12 ) classified NL into three subdomains, namely, functional NL (FNL), the ability to obtain and process nutrition information to improve decisions about nutrition; interactive NL (INL), the ability to utilize different forms of communication to obtain and apply relevant nutrition information; and critical NL (CNL), the ability to critically assess and reflect on nutrition information.…”
Section: Introductionmentioning
confidence: 99%